2008
DOI: 10.1016/j.marenvres.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Hard coastal-defence structures as habitats for native and exotic rocky-bottom species

Abstract: The use of hard coastal-defence structures, like breakwaters and seawalls, is rapidly increasing to prevent coastal erosion. We compared low-shore assemblages between wave-protected and wave-exposed habitats on breakwaters along a sandy shore of Tuscany (North-Western Mediterranean). Assemblages were generally characterized by a low diversity of taxa, with space 5 monopolized by Mytilus galloprovincialis and Corallina elongata on the seaward side of breakwaters and by filamentous algae on the landward side. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 40 publications
5
71
0
Order By: Relevance
“…Assemblages can vary considerably, with some substrates being dominated by fouling species (Bacchiocchi & Airoldi 2003, Qvarfordt et al 2006) and others hosting assemblages not unlike those found on natural shores . The majority of studies, however, find that artificial structures are poor surrogates of natural habitats, often supporting less species diversity (Moschella et al 2005, Gacia et al 2007, Vaselli et al 2008, Pister 2009, Ravinesh & Bijukumar 2013, lower abundances (Connell 2001) or different assemblages entirely (Bulleri & Chapman 2010, Megina et al 2013. Seawalls, in particular, have often been compared to natural rocky shores due to their structural similarities -both are hard-substrata, intertidal environments (Chapman & Bulleri 2003, Moschella et al 2005, Pister 2009, Ravinesh & Bijukumar 2013, Aguilera et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Assemblages can vary considerably, with some substrates being dominated by fouling species (Bacchiocchi & Airoldi 2003, Qvarfordt et al 2006) and others hosting assemblages not unlike those found on natural shores . The majority of studies, however, find that artificial structures are poor surrogates of natural habitats, often supporting less species diversity (Moschella et al 2005, Gacia et al 2007, Vaselli et al 2008, Pister 2009, Ravinesh & Bijukumar 2013, lower abundances (Connell 2001) or different assemblages entirely (Bulleri & Chapman 2010, Megina et al 2013. Seawalls, in particular, have often been compared to natural rocky shores due to their structural similarities -both are hard-substrata, intertidal environments (Chapman & Bulleri 2003, Moschella et al 2005, Pister 2009, Ravinesh & Bijukumar 2013, Aguilera et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Realization that these structures generally support lower biodiversity than natural habitats (see for example Chapman 2003Chapman , 2006Chapman & Bulleri 2003;Moschella et al 2005;Vaselli et al 2008;Firth et al 2013a;Browne & Chapman 2014) has focused attention on designing structures that help facilitate specific ecological outcomes (Firth et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, caution is needed as there is evidence that the impacts of natural and artificial rocky reefs on the structure of marine assemblages can differ, while being similar in the way they may affect the environment (e.g. wave exposure) (Barros et al, 2001;Knott et al, 2004;Vaselli et al, 2008).…”
Section: Discussionmentioning
confidence: 99%